Studi Literatur Pengelolaan Agroforestri Berbasis Kakao di Nusa Tenggara Timur - Aah Ahmad Almulqu; Flora Evalina Ina Kleruk; Dimaz Danang Al-Reza; Dwi Wahyuni; Khozanah Syifa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Cocoa is an important plantation commodity with a significant role in Indonesia's economy. This research aims to understand cocoa-based agroforestry by leveraging traditional management in Sikka Regency, East Nusa Tenggara Province. The study analyzes the cocoa management practices of smallholder cocoa farmers in Sikka Regency. Qualitative research methods are used to gain understanding of the local community's traditional management of cocoa-based agroforestry from focused literature study. The research results are expected to provide a better understanding of cocoa cultivation and conservation practices of smallholder farmers in the region, and to offer recommendations for enhancing productivity and sustainability of cocoa plantations in Sikka Regency